Characterization of cellulose and pulp obtained from rice straw plants of diferent pulping process using scanning eletron microscpy (SEM) - Suhardy, Daud; Mustaffa, Nawawi; Wan Su, Haron; Farizul Hafiz, Kasim; Saiful Azhar, Saad (Universiti Teknologi Malaysia (UTM), 2009)
Organized by Jabatan Kimia , Falkulti Sains, Universiti Teknologi Malaysia (UTM), 12th - 14th September 2005, Hotel Hilton, Kuala Lumpur.